MALE AND FEMALE STUDENTS’ LEARNING STRATEGIES IN MASTERING ENGLISH VOCABULARY - Wiwi Arianti; Radiah Hamid; Sujariati (FKIP Unismuh Makassar, 2022)
The objective of this research is to describe the learning strategies used by male and female students in mastering English vocabulary at MTS Ma’ Arif Banyorang. This Research used a qualitative descriptive. The population in this study is Seventh Grade Students of MTS Ma’ Arif Banyorang. In this research used purposive Sampling Technique in determining the sample. So, the total sample is 15 students. The Instrument of the research is interview with in-depth interview in order to elicit detailed information for the objective of the research. The results of the research shows that the vocabulary learning strategies for male, the strategies are (1) Watching movies, (2) Listening to music, Podcasts, YouTube, (3) Playing game. Meanwhile, the vocabulary learning strategies for female are (1) Memorizing, (2) Reading books, journals, articles, (3) Practicing speaking alone by the mirror, (4) Grouping Discussion. Bases on the findings the conclusion of the research is Male and Female students tend to employ Cognitive strategy as the dominant strategies to improve their vocabulary whereas Determination strategy became the least strategies that students used for vocabulary mastery at Seventh Grade students of Mts Ma’ Arif Banyorang.